Integration and Labour Markets in European Border Regions - Annekatrin Niebuhr; Silvia Stiller (Hamburg Institute of International Economics (HWWA), 2004)
Border regions are likely to play a critical role within the spatial dynamics initiated by the enlargement of the EU. This paper deals with the effects of integration on labour markets in border regions. Within the framework of different theoretical approaches, the effects of integration on labour markets in border regions are analysed. Furthermore, we investigate empirically the degree of labour market integration in European border regions. As indicators for the intensity of integration among neighbouring labour markets measures of spatial association are applied. Results of an analysis of per capita income and unemployment for the period from 1995 to 2000 point to a measurable spatial segmentation of labour markets between EU15 countries along national borders. On average, border regions in the EU are characterised by a lower degree of labour market integration with neighbouring regions than non-border areas due to significant border impediments that hamper equilibrating forces between labour markets on both sides of national frontiers.
Keywords: F22; R23; J61; 330; European Integration; Labour Market Disparities; Border Regions; Spatial Dependence; Grenzgebiet; Arbeitsverwaltung; Marktintegration; EU-Erweiterung; Europäische Integration; Regionale Disparität; EU-Staaten; Osteuropa